Resistencia de Streptococcus bovis aislados de mastitis bovina frente a penicilina y macrólidos-lincosamidas - Denamiel, G. (2013)
The aim of this study was to determine the resistance profile of relevant therapeutic antibiotics penicillin, erythromycin and lincosamides of bovine mastitis isolated Streptococcus bovis. The resistance percentage and minimum inhibitory concentrations (MIC50, MIC90) of 39 phenotypically identified strains were determined. For penicillin, the resistance percentage was 67.6%, the CIM50 0.5?g/mL, CIM90 16 ?g/mL and the range 0.007 to 32 ?g/mL. In the case of erythromycin resistance obtained was 41.2% MIC50 0.125 ?g/mL and MIC90 8 ?g/mL and a range of 0.015-256 ?g/mL. For lincomicyn, resistance obtained was 64.8%, MIC 50 and MIC90 4 ?g/mL and a range of 0.0625- 32 ?g/mL. The identification and antibiotic susceptibility profile of streptococci species provide relevant data for the correct management and control of this mammary disease. Up to now there is few information regarding antibiotic resistance of Streptococcus bovis isolated to bovine mastitis.